Killing Machine : the American Presidency in the Age of Drone Warfare. - Gardner, Lloyd C. (New Press, The, 2013)
With Obama's election to the presidency in 2008, many believed the United States had entered a new era: Obama came into office with high expectations that he would end the war in Iraq and initiate a new foreign policy that would reestablish American values and the United States' leadership role in the world. In this shattering new assessment, historian Lloyd C. Gardner argues that, despite cosmetic changes, Obama has simply built on the expanding power base of presidential power that reaches back across decades and through multiple administrations. The new president ended th.